Using 21st Century Science to Improve Risk-Related Evaluations - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Over the last decade, several large-scale United States and international programs have been initiated to incorporate advances in molecular and cellular biology, -omics technologies, analytical methods, bioinformatics, and computational tools and methods into the field of toxicology. Similar efforts are being pursued in the field of exposure science with the goals of obtaining more accurate and complete exposure data on individuals and populations for thousands of chemicals over the lifespan; predicting exposures from use data and chemical-property information; and translating exposures between test systems and humans. Using 21st Century Science to Improve Risk-Related Evaluations makes recommendations for integrating new scientific approaches into risk-based evaluations. This study considers the scientific advances that have occurred following the publication of the NRC reports Toxicity Testing in the 21st Century: A Vision and a Strategy and Exposure Science in the 21st Century: A Vision and a Strategy. Given the various ongoing lines of investigation and new data streams that have emerged, this publication proposes how best to integrate and use the emerging results in evaluating chemical risk. Using 21st Century Science to Improve Risk-Related Evaluations considers whether a new paradigm is needed for data validation, how to integrate the divergent data streams, how uncertainty might need to be characterized, and how best to communicate the new approaches so that they are understandable to various stakeholders.
Keywords: Environment and Environmental Studies

New Strategies for America's Watersheds - National Research Council (The National Academies Press, 1999)
Emergence of a toxic organism like pfisteria in tributaries of the Chesapeake Bay has focused public attention on potential hazards in our water. More importantly, it has reminded us of the importance of the entire watershed to the health of any body of water and how political boundaries complicate watershed management. New Strategies for America's Watersheds provides a timely and comprehensive look at the rise of "watershed thinking" among scientists and policymakers and recommends ways to steer the nation toward improved watershed management. The volume defines important terms, identifies fundamental issues, and explores reasons why now is the time to bring watersheds to the forefront of ecosystem management. In a discussion of scale and scope, the committee examines how to expand the watershed from a topographic unit to a framework for integrating natural, social, and economic perspectives as they share the same geographic space. The volume discusses:
Keywords: Earth Sciences; Environment and Environmental Studies

Engineering Within Ecological Constraints - National Academy of Engineering (The National Academies Press, 1996)
Engineering within Ecological Constraints presents a rare dialogue between engineers and environmental scientists as they consider the many technical as well as social and legal challenges of ecologically sensitive engineering. The volume looks at the concepts of scale, resilience, and chaos as they apply to the points where the ecological life support system of nature interacts with the technological life support system created by humankind. Among the questions addressed are: What are the implications of differences between ecological and engineering concepts of efficiency and stability? How can engineering solutions to immediate problems be made compatible with long-term ecological concerns? How can we transfer ecological principles to economic systems? The book also includes important case studies on such topics as water management in southern Florida and California and oil exploration in rain forests. From its conceptual discussions to the practical experience reflected in case studies, this volume will be important to policymakers, practitioners, researchers, educators, and students in the fields of engineering, environmental science, and environmental policy.
Keywords: Environment and Environmental Studies; Earth Sciences